Gender, globalisation and the gallows: women sentenced to death for drug trafficking in Malaysia - Harry, L (2022)
A disproportionate number of foreign national women are sentenced to death for drug trafficking in Malaysia, where there is the largest recorded female death row in Southeast Asia; latest disaggregated statistics suggest that there are 141 women on death row, 95% of whom for drug trafficking and 86% of the female death row population are non-citizens. Accordingly, this thesis seeks to address the notable dearth of scholarship on women under sentence of death, particularly for drug trafficking (current analyses focus on the death penalty for homicide). In so doing, it addresses the gap in the literature on the death penalty in Asia, as despite 95% of the world’s executions occurring on this continent, it has received far less attention than other capital punishment regimes. Overall, this thesis engages with the theorising on the criminalisation of women in a globalised era, the literature on the feminisation of migration, existing work on female cross-border informal traders, as well as research on the criminalisation of female migrant workers in the Asian context. It draws upon findings from 47 ‘elite’ interviews with lawyers, judges, Non-Governmental Organisation (NGO) activists, consular officials, police, prosecutors and religious counsellors involved with these women’s cases, as well as systematic searches of legal and media databases which provide information on 146 women’s cases between the years 1983-2019. The analysis of the empirical data involves a conceptual engagement with notions of gendered precarity (chapter 5), gendered disposability (chapter 6), and an examination of the connection between drug trafficking and human trafficking in Southeast Asia (chapter 7). It draws on these findings to examine the undue impact of the mandatory death penalty for drug trafficking on economically precarious foreign national women (chapter 8), contributing to the burgeoning death penalty abolitionist literature.